FACTORS AFFECTING THE SPEED OF CERTIFICATE ACCEPTANCE OF FUNCTIONALITY - Andhyni Kusumahastiti; Suprapto Siswosukarto; Henricus Priyosulistyo (Program Studi Arsitektur S-2 Universitas Pendidikan Indonesia, 2022)
Topic of this research was carried out in relation to the Regulation of the Minister of Public Works 25/PRT/M/2007 concerning the Certificate of Feasibility of Function (SLF). The factors affecting the speed of getting the certificate will be investigated. Each region is required to make further regional regulations that refer to the Regulation of the Minister of Public Works 25/PRT/M/2007. Such a regional regulation can affect the speed and quality of results. The case studies selected in this study were SLF at the Microbiology Building, FKKMK UGM and Hotel de Braga, Bandung. This research based on the results of interviews and data obtained in the microbology building UGM Yogyakarta and Hotel de Braga Bandung. The factors that influence the SLF application process are socialization related to SLF, human resources in the application and issuance process, and understanding of the main tasks and functions of each related human resource. The difference requirements and procedures of the regional regulations does not affect each process but does affect the duration of the SLF issuance process. Substantially, the regional regulations in Sleman Regency has no differences compared to the regional regulations in the city of Bandung regarding SLF but sequence.